(untitled) (Research, Society and Development, 2024)
Colorectal Cancer (CRC) is one of the most prevalent neoplasms in Brazil. The natural history of this neoplasm is well established. Benign lesions initially cause no symptoms and take an average of 10 years to transform into a malignant lesion, making CRC an ideal target for screening and prophylaxis programs. The general objective is to evaluate the knowledge of doctors at Basic Health Units (UBS) in Teresina about CRC screening, and whether they suggest preventive exams to patients. This article was a cross-sectional quantitative and qualitative study, assessing the knowledge of doctors from the Family Health Strategy (ESF) on CRC screening. The survey was answered by 167 doctors, 128 (76.6%) of whom believe they have the knowledge to screen for CRC, 70.7% of doctors claimed not to request screening due to the unavailability of colonoscopy. Finally, it was concluded that the absence of colonoscopy does not justify not carrying out screening, as fecal occult blood testing (PSOF) is a screening method present in Basic Health Units (UBS). In relation to patient resistance and the long queue to be able to take the exams, campaigns should be carried out to raise awareness among the population and provide faster means for carrying out screening. Finally, the research results point to the need to disseminate this topic to the medical population, in order to increase the percentage of doctors who carry out screening and mitigate morbidity and mortality due to CRC.